Perbandingan Algoritma A* Dengan Algoritma Greedy Pada Penentuan Routing Jaringan - Lukman Lukman; Rahmat Hidayat; Muhammad Fachrul Risqi Pribadi (Universitas Raharja, 2019)
The increasing development of the Internet today is in line with the complexity of on line on the internet. So the Network flow optimization became the main problems related to the election of the shortest route (routing protocol). Focus on research is to find out and compare the process with the shortest route in the search algorithm is Greedy algorithm and A * in order to reduce the workload of the network. Model comparison algorithm that is done is look at the workings of each algorithm against the determination of the routing path from the sender to the receiver. On the basis of the implementation of the experiment it was found that the algorithm a * greedy algorithm finds its way with the same. but it is clear for the a * would be more effective if applied on a broad network as well as complicated. Because the calculation uses a * definite while greedy simply looked at what is the most short front side towards the next node that was selected when the end result can be greater than the calculation of a